Exosomes loaded with programmed death ligand-1 promote tumor growth by immunosuppression in osteosarcoma. Issue 2 (20th December 2021) - Zhang, Lei; Xue, Lili; Wu, Yanjuan; Wu, Qilong; Ren, Hongwei; Song, Xiang
ABSTRACT: Osteosarcoma (OS) is a malignant tumor commonly observed in adolescents, who experience relapse and metastasis (30% of the total cases). Its progression is attributed to immune escape mediated by immune checkpoints. However, the intercellular connection between tumor cells and T cells remain unclear. This study was conducted to explore the effects of PD-L1-loaded exosomes on the tumor growth of OS. The exosomes were extracted from cells and tissues through ultracentrifugation. IFN-γ production was determined to evaluate the activity of Jurkat cells. The in vivo growth of OS cells was examined using a C3H xenograft model in mice, tumor volumes were monitored, and the proportion of CD3 + T cells in tumor tissues was detected. Results revealed that PD-L1 was significantly upregulated in the OS cell lines. MG63 and Saos-2 cells were the most abundant in PD-L1, so they were selected as investigation targets. PD-L1 was found to be also highly expressed in the exosomes isolated from MG63 and Saos-2 cells. The exosomes elicited significant inhibitory effects on IFN-γ secretion in Jurkat cells, which were abolished by the PD-L1 antibody or siRNAs. The in vivo growth of C3H cells was significantly facilitated by the overexpression of mPD-L1 or by the administration of mPD-L1-overloaded exosomes. The infiltration of CD3 + T cells was also decreased. The exosomes extracted from clinical PD-L1-positive OS tissues showed a promising inhibitory property against activated T cells. Therefore, PD-L1-loaded exosomes extracted from OS cells aggravated OS progression by suppressing T cell activities. Graphical abstract: uf0001